IMPACTO DE LA PESCA ARTESANAL EN LA EXTINCION DE LA POBLACIONES DE PECES NATIVOS DEL RIO VINCES, EN EL TRAMO COMPRENDIDO DESDE EL LIMITE CANTONAL VINCES-PALENQUE HASTA LA PARROQUIA ANTONIO SOTOMAYOR Y SU EFECTO EN EL DESARROLLO SOSTENIBLE. - JAIME MENDOZA OCHOA (2007)
IMPACT OF ARTISAN FISHING ON THE EXTINCTION OF THE NATIVE FISH POPULATIONS OF THE VINCES RIVER, IN THE SECTION FROM THE VINCES-PALENQUE CANTONAL LIMIT TO THE ANTONIO SOTOMAYOR PARISH AND ITS EFFECT ON SUSTAINABLE DEVELOPMENT.